2023
DOI: 10.3390/biomimetics8020258
|View full text |Cite
|
Sign up to set email alerts
|

Research on Walking Gait Planning and Simulation of a Novel Hybrid Biped Robot

Abstract: A kinematics analysis of a new hybrid mechanical leg suitable for bipedal robots was carried out and the gait of the robot walking on flat ground was planned. Firstly, the kinematics of the hybrid mechanical leg were analyzed and the applicable relevant models were established. Secondly, based on the preliminary motion requirements, the inverted pendulum model was used to divide the robot walking into three stages for gait planning: mid-step, start and stop. In the three stages of robot walking, the forward an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Hence, we predicted that the RP’s collision posture and joint angular velocity are likely to affect the final position and landing posture of the human body. This is similar to the previous studies which found that gait is likely to affect the trajectory of pedestrians [ 23 ] or humanoid robots [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, we predicted that the RP’s collision posture and joint angular velocity are likely to affect the final position and landing posture of the human body. This is similar to the previous studies which found that gait is likely to affect the trajectory of pedestrians [ 23 ] or humanoid robots [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…Humanoid robot research has been a hot topic in various fields since its inception. The humanoid running robot achieves the effect of stable walking by applying the theory to the joints and center of mass of the robot [ 9 ]. At present, many researchers have achieved good simulations of real walking situations, with high bionicity [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three contributions in this Special Issue deal with these problems. The paper by Peng Sun et al ( 2023) [2] conducts a kinematics analysis of a hybrid mechanical leg for bipedal robots and develops a gait planning strategy based on the inverted pendulum model. Dynamic simulations confirm the robot's stable walking on flat ground, providing insights into gait planning for such robots.…”
Section: Discussion Of the Papersmentioning
confidence: 99%
“…The control strategies applied to these robots can be broadly categorized into two classes: conventional control methods and reinforcement-learning (RL)—based approaches. Notably, conventional control methods, including model predictive control (MPC) [ 8 , 9 ], have found extensive application. In contrast, reinforcement learning (RL)—based techniques empower agents to acquire and enhance their performance from scratch, devising policies to attain specific objectives.…”
Section: Introductionmentioning
confidence: 99%